Acute effects of low vs. high inertia during flywheel deadlifts with equal force impulse on vertical jump performance - Tsoukos, A.; Tsoukala, M.; Papadimitriou, D. M.; Terzis, G.; Bogdanis, G. C. (Sensors, 2025)
Background: Flywheel resistance training has gained popularity due to its ability to induce eccentric overload and improve strength and power. This study examined the acute effects of low- (0.025 kg·m2) versus high-inertia (0.10 kg·m2) flywheel deadlifts, matched for force impulse, on the countermovement jump (CMJ) performance, reactive strength index (RSI) during drop jumps (DJs), and rating of perceived exertion (RPE). Methods: Sixteen trained participants (twelve men, and four women) performed three conditions in a randomized, counterbalanced order: low-inertia (LOW), high-inertia (HIGH), and control (CTRL). In the LOW and HIGH conditions, we used force plates to measure and equalize the force impulse in the two conditions (HIGH: 20182 ± 2275 N·s vs. LOW: 20076 ± 2526 N·s; p > 0.05), by calculating the number of deadlift repetitions required to achieve it (HIGH: 5 repetitions and LOW: 9.8 ± 0.4 repetitions). The RSI and CMJ performance were measured pre-exercise, immediately post-exercise, and at 3, 6, 9, and 12 min post-exercise. Results: Both the RSI and CMJ performance improved equally after LOW and HIGH flywheel deadlifts compared to baseline and CTRL (p < 0.01). Specifically, the RSI increased from baseline at 3 to 12 min in both conditions (LOW: 12.8 ± 14.9% to 15.4 ± 14.8%, HIGH: 12.1 ± 17.0% to 12.2 ± 11.7%, p < 0.01), while the CMJ increased from 3 to 9 min in LOW (4.3 ± 3.2% to 4.6 ± 4.7%, p < 0.01) and from 6 to 9 min in HIGH (3.8 ± 4.2% to 4.2 ± 4.9%, p < 0.05). No significant differences were observed between LOW and HIGH conditions (p > 0.05), suggesting similar effectiveness of both inertial loads for enhancing performance. The RPE increased similarly after both conditions from baseline to immediately post-conditioning (LOW: from 2.2 ± 1.2 to 5.8 ± 1.4, HIGH: from 1.5 ± 1.0 to 6.1 ± 1.5, p < 0.01) and decreased by the end of the session, although values remained higher than baseline (LOW: 4.1 ± 1.4, p < 0.01, HIGH: 4.5 ± 2.0, p < 0.01). Conclusions: These findings highlight the potential of flywheel deadlift exercise as an effective method to potentiate explosive performance of the lower limbs, regardless of inertia, provided that the total force impulse is equal.